La Journée internationale des femmes à la télévision française : 1982-2002 - Marlène Coulomb-Gully (Communication)
As subtle as it may be, grasping the dialectic between media and society is no less central in understanding our contemporary universe. This analysis of more than 20 years of television programming around the theme of International Women’s Day confirms it. The analysis allows us, on the one hand, to enter into the editorial strategies of the diverse channels of the « French audio-visual landscape », and on the other, to approach the relationships between media and political agendas, and finally, to issue a few hypotheses concerning the view our national society has on women.